(untitled) (Medical Forum Monthly, 2024)
Introduction: An adequate blood pressure is a treatment of hypertension and it is the risk of cardiovascular morbidity and mortality so proper therapy is essential. Combination therapy of amlodipine plus atorvastatin improved vascular compliance, an indicator of structural and functional vascular changes, and the beneficial effect on small arteries appeared to be more than additive. Objective: This study aimed to evaluate the efficacy and biochemical effects of once-daily optimized Amlodpine/Atorvastatin 5/10 mg (F-6) versus placebo. Study Design: placebo-controlled, comparative study Place and Duration of Study: This study conducted in the Department of Biochemistry, University of Karachi from July 2010 to January 2011. Materials and Methods: This was multicenter, randomized, placebo-controlled, comparative study. Patients were selected from different hospitals of Orangi Town Karachi and samples were analyzed in the department of Biochemistry, University of Karachi. Patients were randomized to receive optimized Amlodpine/Atorvastatin 5/10 mg (F-6) once daily and Placebo once daily for 8 weeks. The efficacy & biochemical effects variables were change from baseline at the end of study which was evaluated. Results: In the patients treated with optimized Amlodipine /Atorvastatin 5/10mg tablets` (F-6) alone, blood pressure reduction was lower, although significant, reaching values of 136.9 ± 10.7 / 88.2 ± 6.3 mmHg (p < 0.05 versus Placebo) by the end of eight weeks of treatment. Thus, the drug regimens used may be considered neutral as regards glucose and significantly reduce LDL-Cholesterol. Conclusion: Due to the high antihypertensive efficacy and hypolipidemic and no biochemical effects of the optimized Amlodipine/Atorvastatin 5mg (F-6) it is an excellent option for the treatment of hypertension and hyperlipidemia patients, with a high potential to reduce cardiovascular risks.